Mucocele salivar com presença de sialólitos, em cadela: relato de caso - Costa, Cintia Kelly Lopes da (Universidade Federal Rural do Semi-Árido, 2017)
The literature shows that the causes that predispose dogs to salivary oral mucoceles, only a small minority may be related to post-traumatic and the cause of most cases has not been determined, and its records related to causes undetermined. However, so far, it has not been possible to induce experimentally the salivary mucocele and found records in the literature that it wasn't possible to induce formation of sialolithiasis salivate associated; the literature has pointed to the possibility that local bone metaplasia and the characteristic of salivary alkalinity in dogs can be determining factors to the occurrence of the disease glândular salivate on this species. It is reported the occurrence of mandibular cervical mucocele associated with sialolithiasis on dog that was treated surgically, having held healing by first intention without complications. It is suggested the possibility of holding other questions not yet addressed in the literature, such as the possibility of failure of ductal salivary ostium in the oral cavity predisposing the occurrence of sialolithiasis in elderly patients, predisposing the contamination by content secondary presence of bacteria and food, with sedimentation that may participate in the 3 formation of concretions sialóticas, deserve to be discussed and evaluated in future studies.
Artigo
Keywords: Metaplasia óssea; Sialolitíase; Concreções ósseas; Bone metaplasia; Sialolithiasis; Bone concretions; CIENCIAS AGRARIAS::MEDICINA VETERINARIA